(untitled) (Bulletin of Innovative Research, 2026)
The article examines the character of Pontius Pilate in Mikhail Bulgakov’s novel "The Master and Margarita" as the embodiment of a moral compromise between personal conscience and national duty. The author examines the psychological nature of the protagonist’s cowardice, defined in the novel as "the most terrible vice," and traces the dynamics of his internal conflict from the moment Yeshua Ha-Notsri sentences him to his metaphysical redemption at the end. Particular attention is paid to the universality of Pilate’s tragedy as a man of power who consciously betrayed the truth for the sake of social well-being. The article substantiates the significance of this character for understanding the philosophical concepts of responsibility and mercy in Bulgakov’s artistic system.